Variáveis nutricionais e nictemerais de dietas com diferentes fontes de lipídeos em ovinos Santa Inês - Pereira, Marília Williani Filgueira (2013)
The aim of this study was to evaluate the inclusion of different fat sources in the diet of lambs over the intake and digestibility of dry matter (DM), organic matter (OM), crude protein (CP), ether extract (EE), neutral detergent fiber (NDF), total carbohydrates (TC), non-fiber carbohydrates (NFC), total digestible nutrients (TDN) and metabolizable energy (ME), microbial production, nitrogen balance (NB), creatinine excretion and nictemeral pattern of feeding behavior. It was used 35 Santa Inês sheep with initial body weight of 13.00 ± 1.80 kg. The experimental design was randomized blocks. The experimental diets consisted of five treatments: the control diet without supplementation, added cottonseed (CAL), bran cashews (FCC), cottonseed meal plus cashews (CALFCC) and calcium salts of long chain fatty acids (CaAgCl). DM intake (kg/day, %PC and g/kg0.75) and nutrients (kg/day) did not change according to the inclusion of dietary lipids, with the exception of EE, NFC intake (kg/day) and NDF (%PC and g/kg0.75). The lipid supplementation influenced the nutrients digestibility, so that diets with CAL showed the lowest digestibility coefficients for DM, OM, NDF and CT (63.89, 64.41, 70.79 and 54.02%), respectively, when compared to the control diet. There was no difference between diets in relation to urinary volume, however the excretions of creatinine were influenced. The NB did not change with the inclusion of lipids, however, purine derivatives excretions (PD mmol/dia), purine derivatives absorption (PD abs. mmol/day), microbial nitrogen production (N microb mmol/day), microbial crude protein (CP microbial g/day) and microbial protein efficiency synthesis (ESPBmic (g)/kgNDT) were influenced by addition of dietary lipids, so that the lowest means for these variables were for diet supplemented with CaAgCl (3.48, 2.95, 2.14, 13.40, 21.31 mmol/day), respectively. The ruminating time (RT), number of chews (No/day), chews per bolus (No/bolus) are influenced in accordance with the addition of lipids in the diet, so that longer times have been expended for the CAL treatment (10,14, 78,91 and 61,026), respectively. The animals fed heavily at times on the periods of 06 to 12 and 12 to 18 h and ruminated in periods that comprised the intervals 18 to 24 and 24 to 06 h. Supplementation with different lipid sources did not influence the consumption of DM and nutrients, with the exception of EE and NFC intake but influences the digestibility of DM and nutrients. NB and urine volume are not affected according to the lipid inclusion in diets, however, the excretions of creatinine are influenced and microbial production is reduced when CaAgcl are part of the diet. The lipid supplementation influences diary cycle patterns on intake behavior in Santa Ines sheep.